Budaya Ta’aruf dalam Pernikahan; Sebuah Tinjauan Sosiologi - Nuzula Ilhami (LPPM IAIN Parepare, 2019)
Ta'aruf today has a big role in the midst of society as a measurable da'wah. Measured in the sense that the da'wah process can be approved, approved and can be evaluated. Ta'aruf is not just a routine worship service, but has developed a collection of rituals that carry out the worship. Moreover, in large cities more and more Ta'aruf communities are providing a place for young people who want to get married. In addition, the Ta'aruf model also extends through the real world or virtual world. Ta'aruf, which initially started from verse contextualization, has now become a community to become an institution that has become a dating agency for teenagers. Ta'aruf is a phenomenal process not only about religion but also the initial capital in the family. Ta'aruf is part of the ukhuwah Islamiyah which is highly recommended by the Islamic religion to its people to get to know each other, both among tribes, nations, and between individuals. Ta'aruf as a process that is in the frame of morality to know each other and determine themselves before going to the level of marriage in accordance with Islamic rules.